Chapter 8: Wobbling with Culturally Proactive Teaching: Facilitating Social Justice through Youth Participatory Action Research with Middle School Students. Issue 13 (April 2021) - Coffey, Heather; Barnes, Meghan
Background: American students represent diverse life experiences, languages, cultures, and community memberships. Given the relatively unchanged demographics of U.S. teachers (primarily middle-class, white females), it is important that teachers engage in culturally proactive pedagogy and design curriculum that both reflects their students' culture and engages them in developing skills to be participants in a larger society. Purpose: This chapter explores how three veteran eighth-grade English language arts teachers in a large middle school in the southeastern United States navigated Youth Participatory Action Research (YPAR) as a culturally proactive and socially just pedagogy and encouraged students to examine power, privilege, and oppression in literature, in informational texts, and in their local communities to identify ways they might change inequities. Research Design: Findings from this qualitative study suggest that even veteran teachers often struggle to implement social justice and culturally proactive pedagogies. Findings: These teachers wobbled with their own uncertainty about the differences between a more traditional pedagogy, where they drive the learning, and a critical pedagogy that places the students in charge of the direction of their learning. Conclusion/Recommendations: From the findings, recommendations are made to teachers who grapple with incorporating socially just and culturally proactive pedagogies into their teaching.